The Service Relationship: Literature Review (International Journal of Scientific Research and Management (IJSRM), 2022)
This article is a literature review on service relationships dealing with two important theoretical approaches in which service relationships are classified: the Perspective Approach and the Interactionist Approach. Then, a service relationship conceptualization is based on the study of several definitions. This literary review also presents service models highlighting the service production process, called “servuction” in the marketing literature (actors and visible and hidden parts of service production). These models also reveal relationships that are concomitant to the service relationship and which condition its success. These relationships are marked by structural tensions. We, equally, present marketing works realized by specialist authors on service relationships which deal with co-production aspects, the shortcomings and the possibilities of improving service relationships. Keywords: service relationship, prescriptive approach, interactionist approach, concomitant relationships, co-production.